The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acssuschemeng.8b05527
|View full text |Cite
|
Sign up to set email alerts
|

Low Dielectric Fluorinated Polynorbornene with Good Thermostability and Transparency Derived from a Biobased Allylphenol (Eugenol)

Abstract: A new biobased functional norbornene was synthesized by the Diels–Alder reaction between cyclopentadiene and the fluorinated eugenol. Based on the norbornene monomer, a new polynorbornene was prepared with a high molecular weight (M n = 78 000 Da) by the standard ring opening metathesis polymerization (ROMP). This polymer displayed good film-forming ability and can be postpolymerized to form a cross-linked network at high temperature (>150 °C) via the [2 + 2] cycloaddition reaction of trifluorovinyl ether (−OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…This high storage modulus of the 4 pbw systems is attributed to the enhanced cross‐link density. [44] The effect of DCP and BIPB on the dynamic mechanical tests was in line with the results of the tensile tests.…”
Section: Resultssupporting
confidence: 76%
“…This high storage modulus of the 4 pbw systems is attributed to the enhanced cross‐link density. [44] The effect of DCP and BIPB on the dynamic mechanical tests was in line with the results of the tensile tests.…”
Section: Resultssupporting
confidence: 76%
“…The global depletion of fossil resources and the environmental issues have generated considerable interest toward the production of renewable chemicals from the biomass as the ubiquitous and renewable feedstock in recent years. Among biomasses, lignin as the second largest quantity of renewable resource becomes an effective substitute for petrochemical-derived chemicals in aromatic polymers with excellent properties. Starting from lignin, a functional compound named vanillin can be easily prepared. , Because vanillin has a naturally aromatic ring and easily modified aldehyde and hydroxyl groups, it is an ideal feedstock for the synthesis of polymers. Therefore, studies on vanillin-based polymers, such as polyesters, polycarbonates, polyvanillin, and polyacetal, have been carried out . However, these polymers are thermoplastic, and they display low glass transition temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many researchers around the world have been focused on the preparation of PFCB polymers [ 27 , 31 , 32 , 33 , 44 , 45 , 46 , 47 , 48 , 49 , 60 , 61 , 62 , 63 , 64 ]. Monomers containing TFVE moieties have been developed and used to obtain PFCB polymers [ 31 , 60 , 61 , 62 ]. PFCB precursors bearing organic-inorganic cores including siloxanes and polyhedral oligomeric silsesquioxanes (POSS) have also been reported [ 28 , 65 , 66 ].…”
Section: Synthesis Of Pfcb Polymersmentioning
confidence: 99%
“…Fang et al [ 61 ] recently reported the utility of eugenol to produce a new norbornene, TFVE-containing monomer, which can be polymerized into a crosslinked network containing PFCB moieties ( Scheme 8 ). Eugenol has become popular as a renewable bio-feedstock for the synthesis of new high-performance materials due to its ready availability at low cost and reactive hydroxyl and unsaturated functional groups [ 70 ].…”
Section: Synthesis Of Pfcb Polymersmentioning
confidence: 99%